TiCl4-promoted condensation of methyl acetoacetate, isobutyraldehyde, and indole: a theoretical and experimental study. Issue 14 (9th March 2015) - Renzetti, Andrea; Marrone, Alessandro; Gérard, Stéphane; Sapi, Janos; Nakazawa, Hiroshi; Re, Nazzareno; Fontana, Antonella
Abstract : A combined DFT and experimental study of the title reaction points to a three-step mechanism: (1) titanium enolate formation, (2) Knoevenagel condensation of enolate and aldehyde, and (3) Michael addition of indole. Abstract : The mechanism of the TiCl4 -promoted condensation of methyl acetoacetate, isobutyraldehyde, and indole was studied by a combination of theoretical and experimental techniques. The energy profile of plausible reaction paths was evaluated by DFT calculations, and various reaction intermediates were isolated or observed in solution by NMR spectroscopy. Theoretical and experimental results indicate that the reaction proceeds in three steps, all promoted by titanium: (1) formation of the enolate ion of methyl acetoacetate, (2) Knoevenagel condensation of the enolate ion and aldehyde, and (3) Michael addition of indole to the Knoevenagel adduct. The study sheds light on the role of titanium in the reaction, providing a mechanistic model for analogous reactions.